Optimizing design of research to evaluate antibiotic stewardship interventions: consensus recommendations of a multinational working group. (January 2020) - Schweitzer, V.A.; van Werkhoven, C.H.; Rodríguez Baño, J.; Bielicki, J.; Harbarth, S.; Hulscher, M.; Huttner, B.; Islam, J.; Little, P.; Pulcini, C.; Savoldi, A.; Tacconelli, E.; et al.
Abstract: Background: Antimicrobial stewardship interventions and programmes aim to ensure effective treatment while minimizing antimicrobial-associated harms including resistance. Practice in this vital area is undermined by the poor quality of research addressing both what specific antimicrobial use interventions are effective and how antimicrobial use improvement strategies can be implemented into practice. In 2016 we established a working party to identify the key design features that limit translation of existing research into practice and then to make recommendations for how future studies in this field should be optimally designed. The first part of this work has been published as a systematic review. Here we present the working group's final recommendations. Methods: An international working group for design of antimicrobial stewardship intervention evaluations was convened in response to the fourth call for leading expert network proposals by the Joint Programming Initiative on Antimicrobial Resistance (JPIAMR). The group comprised clinical and academic specialists in antimicrobial stewardship and clinical trial design from six European countries. Group members completed a structured questionnaire to establish the scope of work and key issues to develop ahead of a first face-to-face meeting that (a) identified the need for a comprehensive systematic review of study designs in the literature and (b) prioritized key areas where research design considerations restrict translation of findings into practice. The working group's initial outputs were reviewed by independent advisors and additional expertise was sought in specific clinical areas. At a second face-to-face meeting the working group developed a theoretical framework and specific recommendations to support optimal study design. These were finalized by the working group co-ordinators and agreed by all working group members. Results: We propose a theoretical framework in which consideration of the intervention rationale the intervention setting, intervention features and the intervention aims inform selection and prioritization of outcome measures, whether the research sets out to determine superiority or non-inferiority of the intervention measured by its primary outcome(s), the most appropriate study design (e.g. experimental or quasi- experimental) and the detailed design features. We make 18 specific recommendation in three domains: outcomes, objectives and study design. Conclusions: Researchers, funders and practitioners will be able to draw on our recommendations to most efficiently evaluate antimicrobial stewardship interventions.